Applying the Waterfall Method and Temporal Overlap Detection Algorithm in a Cross-Platform Badminton Court Booking Application - Danis Wara Wardana; Joko Sutopo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study directly addresses the specific scheduling bottlenecks and operational inefficiencies at Furry Sport Center Seyegan, Sleman. The conventional booking workflow, dependent on manual physical logbooks and fragmented WhatsApp communications, suffers from severe limitations such as high vulnerability to double bookings and delayed staff responses. The digitalization of this management system is highly urgent to prevent ongoing operational disruptions and potential revenue loss caused by these manual errors. To resolve this, a cross-platform mobile booking application was developed utilizing the Waterfall software development model, engineered with a Flutter and Node.js architecture. The system incorporates a Temporal Overlap Detection Algorithm to systematically ensure conflict-free scheduling. To provide objective evidence of efficiency and eliminate subjective claims, system validation was conducted using the System Usability Scale (SUS). The testing yielded an overall average score of 79.25, placing the application in the acceptable usability category with high user satisfaction. These empirical parameters demonstrate that the application measurably resolves conventional scheduling conflicts and provides a proven, transparent solution for local sports venue management.